Influence of Cone Collection Date on Seed and Germination Characteristics in Blue Pine, Pinus wallichiana Ab. Jacks - Lavania, S. K.; Singh, Virendra; Prasad, Birendra (Indian Forester, 2010)
The present study deals with the effect of cone collection date on seed and germination characteristics in blue pine (Pinus wallichiana). The first cone collection was done on 15th September, second on 30th September, third on 15th October and fourth on 30th October from Gangotri range of Uttarkashi Forest Division of Garhwal Himalaya. Percentage of viable seeds, per cone increased while percentage of non-viable seeds per cone decreased with the maturity of cone. Mean fresh weight of 100 seeds increased from first to fourth (last) cone collection date. The moisture content of seeds decreased while seed germination increased as cone collection dates progressed. Germination per cent and germination value of seeds steadily increased from cone collection date of 15th September to 30th October. Therefore, the cones should be collected in the last week of October to obtain quality seeds.